VIABILITAS RAGAM HIAS SULUR GELUNG TERATAI - Akhmad Nizam; Wisma Nugraha Ch R.; SP. Gustami (Institut Seni Indonesia Yogyakarta, 2019)
The walls of Hindu and Buddhist temples in Java are often found in the carved ornament of lotus plants that is grown from tubers or urns. In early period of Islam in Java, the existence of this decorative variety remained. Based on the books of the Hindu Purana, there is an explanation of the concept of the the universe creations embodied in the form of lotus scrolls. Meanwhile, from the old manuscripts belonging to the Wali, although limited in the scope of Sufism of the Tarekat Syaththariyah there is an explanation of the lotus with the name of the Tunjung flower. This article discusses the concept of creating works of art based on the theory of adaptation by Linda Hutcheon in his book: A Theory of Adaptation. The discussion is more emphasized on the visual aesthetic aspects contained in Lara Jonggrang Prambanan temple in Kalasan Yogyakarta, Surowono Temple in Kediri East Java and Sunan Drajat tomb in Lamongan, East Java. The ornamental variety, whose concept of creation was adapted from Purana books of Hindu, was in early Islam believed to follow the theoretical procedures, as well as in later times, but the philosophical meaning may be less well known. Keywords: ornament, sulur gelung, padmamūla, tunjung Dinding candi-candi Hindu dan Buddha di Jawa, sering ditemukan pahatan ragam hias sulur tumbuhan teratai yang tumbuh dari bonggol atau guci bergelung-gelung. Pada masa Islam awal, eksistensi ragam hias ini tetap bertahan. Berdasarkan kitab-kitab Purana Hindu, terdapat penjelasan mengenai konsep pembentangan alam semesta yang diwujudkan dalam bentuk gulungan teratai. Sementara itu, dari naskah lama milik para Wali, meskipun terbatas dalam lingkup tasawuf Tarekat Syaththariyah terdapat penjelasan mengenai teratai dengan nama bunga tunjung. Artikel ini membahas tentang konsep penciptaan karya seni berdasarkan teori adaptasi oleh Linda Hutcheon dalam bukunya: A Theory of Adaptation. Pembahasan lebih ditekankan pada aspek-aspek estetis visual yang terdapat di candi Lara Jonggrang Prambanan di Kalasan Yogyakarta, Candi Surowono di Kediri Jawa Timur dan makam Sunan Drajat di Lamongan Jawa Timur. Ragam hias tersebut, yang konsep penciptaannya diadaptasi dari kitab-kitab purana Hindu, maka pada masa Islam awal diyakini mengikuti prosedur teori tersebut, begitu juga pada masa berikutnya, tetapi makna filosofisnya mungkin kurang begitu dikenal. Kata kunci: ragam hias, sulur gelung, padmamūla, tunjung